2020
DOI: 10.2174/1874285802014010057
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus Associated with Head and Neck Squamous Cell Carcinoma in Jordanian Patients

Abstract: Background: In addition to smoking and alcohol consumption, human papillomavirus (HPV) is a leading etiology for Head and Neck Squamous Cell Carcinoma (HNSCC). However, this causal association is still understudied in Middle Eastern populations. Objective: The aim of this study was to determine the prevalence of HPV-associated infection in the Jordanian HNSCC patients and the associated HPV genotypes. Methods: Formalin-Fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…The moderately-differentiated are observed with HPVnegative while poorly differentiated are associated with HPV-positive HNSCC, however, no such association was observed in our study. 20,24,25 While our findings are consistent with many of the reported studies in literature, it is arduous to compare various local published studies on HPV-16 mainly due to the wide discrepancy in findings. Plausible reasons of this discrepancy are variations in sample size, type of sample used for instance tissue, saliva, oral scraping or saliva-rinse, techniques employed for HPV-16 detection and studies involving only one subset of HNSCC mainly oral or oropharyngeal squamous-cell-carcinoma.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The moderately-differentiated are observed with HPVnegative while poorly differentiated are associated with HPV-positive HNSCC, however, no such association was observed in our study. 20,24,25 While our findings are consistent with many of the reported studies in literature, it is arduous to compare various local published studies on HPV-16 mainly due to the wide discrepancy in findings. Plausible reasons of this discrepancy are variations in sample size, type of sample used for instance tissue, saliva, oral scraping or saliva-rinse, techniques employed for HPV-16 detection and studies involving only one subset of HNSCC mainly oral or oropharyngeal squamous-cell-carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…19 In the present study, the smoking rate (46%) in a form of cigarette, bidi and hookah was high compared to chewed tobacco and alcohol in HNSCC patients, however, no significant association was found between overall use of tobacco and HPV-16 which is in agreement with previous study. 20 Our data indicate that both tobacco and HPV-16 are independent risk factors for tumorigenesis of HNSCC in Punjab (the largest province of Pakistan). In contrast, previous study reported significant association between HPV-16 and chewed tobacco users.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…HPV-positivity according to oropharyngeal subsites was reported in 19 studies (48,250). Ten studies reported the highest HPV+ rate in palatine tonsillar squamous cell carcinoma (TSCC) ( n = 47,690) [ 4 , 19 , 20 , 21 , 28 , 32 , 33 , 34 , 35 , 36 ], and three reported the highest HPV+ rate in base of tongue squamous cell carcinoma (BTSCC) ( n = 2 51) [ 29 , 37 , 38 ].The proportion of HPV-positivity among patients with TSCC varied from 15% to 86%, among patients with BTSCC from 1% to 82%, and for other oropharyngeal locations from 1% to 100%, Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…HPV detection methods varied among the included studies. Fifteen studies were based on double positivity with both HPV DNA PCR and p16 IHC ( n = 6624) [ 4 , 16 , 19 , 20 , 22 , 23 , 28 , 30 , 32 , 33 , 34 , 35 , 38 , 39 , 40 ], eight studies were based on HPV DNA alone ( n = 426) [ 12 , 14 , 15 , 24 , 25 , 29 , 36 , 41 ], six on p16 alone ( n = 391) [ 17 , 18 , 21 , 26 , 27 , 31 ], one study was based on both HPV DNA and HPV RNA ( n = 99) [ 37 ] and one study did not report a detection method ( n = 42,024) [ 13 ]. Most studies using p16 IHC defined p16-positivity (p16+) according to ASCO guidelines with ≥70% positive staining [ 42 ] ( n = 2663), but one study defined p16+ as ≥10% positive staining ( n = 30) [ 30 ], four studies defined p16+ as ≥75% positive staining ( n = 2678) [ 4 , 22 , 31 , 32 ] and one study did not account for p16-positivity ( n = 926) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%